WEAR RESISTANCE OF MONOLITHIC CONCRETE INDUSTRIAL FLOORS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article is devoted to the urgent problem of increasing the wear resistance of monolithic concrete industrial floors experiencing the aggression of industrial environments. It shows the improvement of cement concrete structure by introducing modifying additives into concrete composition, improving deformative and strength properties of concrete coatings and providing compaction of its surface, reducing surface abrasion.